Шахтные исследования состояния наклонных выработок - Халимендик, Ю.М.; Панибратченко, В.Ф.; Терещук, Р.Н.; Колесниченко, Е,А.; Григорьев, А.Е. (Геотехническая механика, 2011)
Наведена методика виконання шахтних досліджень. Наведені результати візуальних та
інструментальних шахтних досліджень стану похилих виробок ТДВ «Шахта Білозерська».
Виявлено основні види деформацій приконтурного масиву та кріплення. Отримані залеж-
ності стійкості похилих виробок за глибиною. Виконано аналіз отриманих залежностей. A method for the implementation of mining research is shown. These results of visual and instrumental study of the state of inclined workings of mining company "Mine Belozerskaya" are
given. The basic types of deformations of the surrounding array and roof supports are defined.
The resulting dependence of the stability of inclined workings on depth are achieved. The
analysis of the obtained dependences is done